Africapitalism : sustainable business and development in Africa - Idemudia, Uwafiokun; Amaeshi, Kenneth (Routledge, 2019)
Using theory, empirical research, and case studies, this book explores the changing nature of business in Africa and how businesses can actively contribute to the development of Africa. It uses (and critically analyses) the concept of Africapitalism - a management philosophy and movement which seeks to blend the best of African values and Western management theories as a basis for sustainable development in Africa - to understand the subtle factors that underpin business decisions in Africa. The collection of chapters in this book are organized around actors, issues, and reflections. They collectively present an account of Africapitalism, albeit from different perspectives and on different issues, and open up a new space for rethinking business and society relations in Africa from an Africapitalism perspective. Crucial is the critical engagement with both the discourse and practice of Africapitalism and its implications for sustainable development. It is anticipated that the challenges and opportunities highlighted by the book would be embraced by researchers, policy makers, and practitioners in the broad area of business and society in Africa This multidisciplinary book will be valuable reading for advanced students, researchers and policymakers looking at business in society; corporate social responsibility; sustainable business; international business and African development--Provided by publisher.